The Potential Application of the GNSS Leveling Method in Local Areas by Means of Sector Analysis - Fedorchuk, Alina (Geomatics and Environmental Engineering, 2022)
The purpose of this work is to perform the comparison of heights of global geoid models EGM08, EIGEN-6C4, GECO, and XGM2019e based on sector analysis that are obtained relative to the ellipsoid WGS84 and GRS80 in order to implement the method of GNSS leveling in local areas. The heights of the global geoid models determined from the ellipsoid WGS84 should be reduced by âˆ’41 cm ("œzero-degree term") in order to scale them to the calculated geoid by GNSS leveling. Heights determined from the ellipsoid GRS80 should be increased by +52 cm. Spatial analysis of the heights of geoid models in the relative system for the northern territory shows that the standard deviation of the heights of geoid models is 13.6 cm, and for the southern territory it is 36.5 cm. The elevation errors of the geoid models in the relative system were estimated to be standard deviations of 2.9 cm within the northern area and 2.3 cm within the southern one. The root mean square values of initial errors of the models EGM08, EIGEN-6C4, GECO, and XGM2019e are 8.6 cm, 4.6 cm, 4.4 cm, and 3.8 cm, respectively, and standard deviation values are 2.0 cm, 2.2 cm, 3.2 cm, and 2.4 cm. The paper also performs a sector analysis of the geoid model errors in order to correct them for the application of the GNSS leveling method within the research area. The standard deviations of the residual error of the corrected model heights are 1.8 cm, 1.9 cm, 2.5 cm, and 2.0 cm for EGM08, EIGEN-6C4, GECO, and XGM2019e. The root mean square values of these residual errors for the geoid models are 1.9 cm, 2.0 cm, 2.5 cm, and 2.0 cm, respectively.